PEMBUATAN TAMAN BACA RAMAH ANAK SEBAGAI UPAYA MENINGKATKAN MINAT BACA PADA ANAK-ANAK DESA BEJIJONG KABUPATEN MOJOKERTO - Anggraeni Cahya Ningrum; Novia Aulia Sari; Isaam Fajar Maulana; Anggraeny Puspaningtyas (ABDIMAS, 2023)
PPK ORMAWA is one of the MBKM activities held by the government to support student education so that it can be directly conveyed to the Indonesian people through students. The PPK ORMAWA activity is an activity that has 5 Literacy Corner Programs, one of which is the Reading Garden Literacy Corner. Bejijong Village is a tourist village where this village is also one of the villages where the average community has a low level of reading interest. So that with the Literacy Corner of a Child Friendly Reading Park in Bejijong Village, now children can have the right Reading Garden. Literacy is the only program supported by the government because Indonesia has a very strong literary culture. This service aims to increase the attractiveness of children in Bejijong Village in the world of literacy. The results obtained are that the ORMAWA PPK Team has made this program. With this place, it is hoped that it can increase the attractiveness of children in Bejijong Village in the world of literacy. So that with this place children can learn and read various books that are already available in that place.